The effects of land use on the avifauna and its conservation in a Kenyan coastal forest ecosystem, and the significance of the Arabuko Sokoke Forest to the local community - Chiawo, David O (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2016)
This study examines the effects of land use on the bird community of Arabuko Sokoke Forest, the largest area of coastal forest remaining in East Africa and a major Important Bird Area in mainland Kenya. Bird species diversity in three land use types (primary forest, plantation and farm lands) was compared using multivariate analysis to determine the response of different feeding guilds to habitat characteristics. The effect of habitat characteristics on overall bird diversity and specific feeding guilds was tested using linear mixed models. A total of 2600 bird observations were recorded during point counts, representing 97 bird species including 25 fruit-eating birds, 17 nectar feeders; and 60 species belonging exclusively to other feeding guilds. Land use had a significant effect on overall bird diversity and abundance. The distribution of frugivorous birds was primarily influenced by the presence of fruiting trees rather than land use type, while nectarivores were significantly affected by vertical habitat heterogeneity and vegetation type. Although the distribution of insectivorous birds is influenced by many habitat factors, proximity to natural forest, habitat heterogeneity, and the presence of large trees and fruiting trees appear to be most important to this guild. The natural forest has the greatest avian diversity and a distinctive community compared to plantation and farmlands. Patterns of habitat use by birds in the area suggest that vertical vegetation heterogeneity and complexity is especially significant in sustaining diverse and abundant bird populations, if they are in close proximity to native forests. Improvement of conservation management for the plantation and farmlands is thus critical for connectivity with other remnant primary forest patches in the area. Socio-economic data was collected from 109 forest adjacent households to determine the value of the forest to the local community and their perception of conservation issues. Arabuko Sokoke Forest is important in supplementing the livelihood needs of the local community. However, the community lacks information on the forest management plan and many people have little knowledge of local birds, which could limit their capacity to participate in conservation projects. Drivers for local community participation in conservation projects are primarily a sustainable income and the fulfillment of basic household needs. Community conservation education is needed to promote local knowledge of forest biodiversity, as well as clear frameworks for the active involvement of the local community in forest management. Support of community based projects is vital to achieve both the conservation and livelihood objectives of the Arabuko Sokoke Forest management plan.
Keywords: Uncatalogued